Obesity and the lung: 4 · Obesity and asthma. Issue 11 (4th November 2008) - Sin, D D; Sutherland, E R
Abstract : Over the past 30 years there has been an epidemic of both obesity and asthma in the western world. A large body of robust epidemiological data has linked obesity with the development and severity of asthma in both children and adults and weight reduction with improvements in asthma severity and symptoms. However, it remains unsettled whether this relationship is causal or confounded by some other factor(s) as mechanistic and physiological studies have produced heterogeneous and at times conflicting findings. This review examines the clinical and epidemiological relationship between obesity and asthma and the purported mechanisms that may link these two processes together.